Area-level deprivation and oral cancer in England 2012–2016. (December 2020) - Ravaghi, Vahid; Durkan, Colum; Jones, Kate; Girdler, Rebecca; Mair-Jenkins, John; Davies, Gill; Wilcox, David; Dermont, Mark; White, Sandra; Dailey, Yvonne; Morris, Alexander John
Highlights: Area-level deprivation was directly linked with oral cancer incidence and mortality. Effect of deprivation on oral cancer was stronger at the end of the deprivation spectrum. Area-level deprivation was an independent risk factor for oral cancer. Abstract: Background: The relationship between deprivation and oral cancer is complex. We examined magnitude and shape of deprivation-related inequalities in oral cancer in England 2012-2016. Methods: Oral cancer was indicated by cancers of the lip and oral cavity (ICD10 C00-C06) and lip, oral cavity and pharynx (C00-C14) and deprivation by the Index of Multiple Deprivation. Deprivation inequality in incidence and mortality rates of oral cancer outcomes was measured using the Relative Index of Inequality (RII). Fractional polynomial regression was used to explore the shape of the relationships between deprivation and oral cancer outcomes. Multivariate regression models were fitted with the appropriate functions to examine the independent effect of deprivation on cancer adjusting for smoking, alcohol and ethnicity. Results: Incidence rate ratios (IRRs) and mortality rate ratios (MRRs) were greater for more deprived areas. The RII values indicated significant inequalities for oral cancer outcomes but the magnitude of inequalities were greater for mortality. The relationships between deprivation and oral cancer outcomes were curvilinear. Deprivation, Asian ethnicity and alcohol consumption were associated with higher incidence and mortality rates of oral cancer. Conclusion: This is the first study, to our knowledge, exploring the shape of socioeconomic inequalities in oral cancer at neighbourhood level. Deprivation-related inequalities were present for all oral cancer outcomes with a steeper rise at the more deprived end of the deprivation spectrum. Deprivation predicted oral cancer even after accounting for other risk factors.